Kobiety w życiu i twórczości Siergieja Jesienina - Popiel-Machnicki, Wawrzyniec (Studia Rossica Posnaniensia, 2012)
The literary criticism of Sergei Yesenin’s poetry notices what is most visible in it: a description of Russia and the native Ryazan region imbued with the religion and rural cosmogony of ancestors. His hedonistic character, which was his tendency towards alcohol consumption and a rich erotic life, was frequently emphasized. This emphasis was to decrease the importance of spirituality in his works. The present article is an attempt at describing the importance of women in Sergei Yesenin’s life and works.